Nutrient elements in grassland : soil-plant-animal relationships - Whitehead, D. C. [ (David Charles)] (CABI, 2000)
This text is a reference source covering the chemical elements that are nutrients for plants and animals. It deals with the concentrations and transformations of these elements in soils, grassland plants, and ruminant aniamls, particularly cattle and sheep